2018
DOI: 10.2147/ijn.s170680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of young exosomes injected in aged mice

Abstract: IntroductionExosomes, nanosized extracellular vesicles, are known to circulate through the blood stream to transfer molecular signals from tissue to tissue.MethodsTo determine whether exosomes affect aging in animals, we primarily identified the changes in exosomal miRNA contents during the aging process. In exosomes from 12-month-old mice, mmu-miR-126-5p and mmu-miR-466c-5p levels were decreased and mmu-miR-184-3p and mmu-miR-200b-5p levels were increased significantly compared with those of 3-month-old mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…In contrast, while exosomes may play a role in the spreading of AD, some studies have shown a positive effect of introducing non-pathogenic exosomes to change disease duration and progression (Table 3). In animal studies, this therapeutic effect was found when exosomes from young mice were observed to significantly downregulate aging-associated signaling molecules such as IGF1R and upregulate telomeraserelated genes such as Men1, Mre11a, Tep1, Terf2, Tert, and Tnks in aged mice (Lee et al, 2018). Furthermore, exosomes injected into the brain of transgenic mouse models of AD can help to decrease toxic oligomers and fibrils in a microglial-dependent manner following intracerebral administration, contributing to the clearance of Aβ in vivo (Yuyama et al, 2012(Yuyama et al, , 2014Yuyama and Igarashi, 2017).…”
Section: Exosomes As Novel Ad Therapeuticsmentioning
confidence: 98%
“…In contrast, while exosomes may play a role in the spreading of AD, some studies have shown a positive effect of introducing non-pathogenic exosomes to change disease duration and progression (Table 3). In animal studies, this therapeutic effect was found when exosomes from young mice were observed to significantly downregulate aging-associated signaling molecules such as IGF1R and upregulate telomeraserelated genes such as Men1, Mre11a, Tep1, Terf2, Tert, and Tnks in aged mice (Lee et al, 2018). Furthermore, exosomes injected into the brain of transgenic mouse models of AD can help to decrease toxic oligomers and fibrils in a microglial-dependent manner following intracerebral administration, contributing to the clearance of Aβ in vivo (Yuyama et al, 2012(Yuyama et al, , 2014Yuyama and Igarashi, 2017).…”
Section: Exosomes As Novel Ad Therapeuticsmentioning
confidence: 98%
“…These nanocarriers contain proteins, lipids, and nucleic acids, which are the major mediators of cell–cell communication and play regulatory roles in several cellular processes such as immune regulation ( Vanni et al, 2017 ; Zhang X. et al, 2019 ). In addition, plasma exosomes from young individuals have been reported to have anti-inflammatory effects on ischemia ( Lee B.R. et al, 2018 ); nevertheless, the mechanism by which exosomes protect nerve cells from ischemia injury remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Among these miRNAs, mmu-miR-184-3p have been observed upregulation in exosome of old mice. 7 Plasma miR-139-3p was found changing in age-related macular degeneration. 8 In addition, miR-186-3p was clarified to regulate cell cycle via targeting cyclin-dependent kinase 1.…”
Section: Discussionmentioning
confidence: 97%